Characterisation of nanosilica modified asphalt binder / Mohamad Saifullah Samsudin - Samsudin, Mohamad Saifullah (2018)
The base asphalt binder has several disadvantages which limits its use in heavily trafficked highway and in high temperature environment due to its low resistance to rutting. Therefore, base asphalt binder is normally modified to enhance its properties. Nanosilica (NS) has been used in many fields to improve the properties of materials due to its enhancing properties such as large surface area, good dispersal ability, strong adsorption, high chemical clarity and excellent stability.